1976
DOI: 10.1111/j.1432-1033.1976.tb10826.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of GTP in Eukaryotic Polypeptide‐Chain Initiation

Abstract: 1.A factor, which makes a ternary complex with GTP and eukaryotic initiator tRNA (MettRNAi), has been purified 100-fold from developed cysts of Artemia salina. Some of the properties of the purified factor have been studied.2. M 2 + appears to inhibit ternary complex formation. 3. Little or no ternary complex is formed when 5 pM GTP is replaced by an identical concentration of UTP, CTP or ATP. The analog, guanosine 5'-(fi,y-imino)triphosphate [GMP-P(NH)P] seems to be a much better substitute for GTP than guano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1977
1977
1982
1982

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Of the nonhydrolyzable analogs of GTP only GMP-P(NH)P could replace GTP and was, indeed, more effective, while GMP-P(CH,)P was only 15% as effective. This is in agreement with the results of Ochiai-Yanagi and Mazumder (1976) who used initiation factor from A . salina, although a number of others have reported that GMP-P(CH,)P could substitute for GTP to some degree in other systems (Dettman and Stanley, 1972;Levin et al, 1973;Walton and Gill, 1975;Harbitz and Hauge, 1976).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Of the nonhydrolyzable analogs of GTP only GMP-P(NH)P could replace GTP and was, indeed, more effective, while GMP-P(CH,)P was only 15% as effective. This is in agreement with the results of Ochiai-Yanagi and Mazumder (1976) who used initiation factor from A . salina, although a number of others have reported that GMP-P(CH,)P could substitute for GTP to some degree in other systems (Dettman and Stanley, 1972;Levin et al, 1973;Walton and Gill, 1975;Harbitz and Hauge, 1976).…”
Section: Discussionsupporting
confidence: 92%
“…When GDP is present in equimolar concentration with GTP, ternary complex formation is inhibited 32% with a purified preparation of initiation factor from A . salina (Ochiai-Yanagi and Mazumder, 1976), 56% in the crude KC1 wash fraction from Ehrlich ascites tumor cells (Smith and Henshaw, 1975), and 60% and 70% in a postribosomal supernatant from rat skeletal and heart muscle, respectively (Rannels et al, 1976). This is to be compared with an 85% inhibition in our brain system when GDP and GTP are added in equimolar amounts (results not shown).…”
Section: Discussionmentioning
confidence: 99%